2017
DOI: 10.1111/ene.13292
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic manifestations in stroke patients treated with intravenous alteplase

Abstract: Intravenous alteplase is not associated with an increased risk of clinical or electroencephalographic epileptic phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Our results support the findings of several smaller studies that did not find an increased number of acute symptomatic seizures in patients undergoing IVT 26,[28][29][30]32 . Some of these studies presented more clinical details of patients suffering from acute symptomatic seizures, but the overall numbers of patients with seizures were limited in most studies, ranging from n = 3 to n = 25.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results support the findings of several smaller studies that did not find an increased number of acute symptomatic seizures in patients undergoing IVT 26,[28][29][30]32 . Some of these studies presented more clinical details of patients suffering from acute symptomatic seizures, but the overall numbers of patients with seizures were limited in most studies, ranging from n = 3 to n = 25.…”
Section: Discussionsupporting
confidence: 92%
“…These discrepancies are probably due to differences in seizure detection, classification and a referral bias in single-center studies with populations from tertiary stroke-centers. While it is known that standard electroencephalographic measurements significantly increase the likelihood of detecting post-stroke seizures 35 , only one study employed routine use of electroencephalography 28 . However, this prospective study did not report an overall seizure frequency 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, intravenous thrombolysis was associated with a threefold higher risk of stroke-related seizures. In contrast, Bentes et al [40] and Tan et al [41] did not reveal any correlation between thrombolysis in the acute stage of stroke and a higher risk of late seizures. Moreover, Nesselroth et al [42] showed that thrombolysis treatment significantly decreased the risk of poststroke epilepsy.…”
Section: Predictors Related To Treatmentmentioning
confidence: 85%
“…Thrombolysis with recombinant tissue plasminogen activator (tPA) is the standard of care for all acute ischemic stroke meeting inclusion criteria, therefore it is important to note that there has been some evidence suggesting an increased risk of post-stroke seizures with the use of tPA [64][65]. However, other studies that did not find a statistically significant difference with regard to increased post-tPA seizure incidence [66][67]. Statins, which are widely used in stroke and cardiac patients for lipid control, on the other hand have been shown to be beneficial against post-stroke seizures [68][69].…”
Section: Management Of Post-stroke Seizuresmentioning
confidence: 99%